APLIKASI iREAP DALAM MENDUKUNG INTERNAL CONTROLPADA SIKLUS PENDAPATAN TOKO RETAIL AKSESORIS PONSEL “X” DI SURABAYA - Jessica Athalia Sutantio; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
This is a qualitative research with the purpose of explanatory research and have the quality of applied research because it is based of the fraud problem in revenue cycle. Internal control is an important thing because it gives assurance to achieve an organization’s goal. If the internal control is weak, then it will cause problem in the revenue cycle. Revenue cycle is a cycle where there is a cash inflow in an organization. If this inflow is obstructed, then it can affect the operational of the company, so it needs internal control. The basic theory that used is COSO Internal Control Framework, because it is used either internationally or nationally. The object used in this thesis is “Toko X” and the methods used are interview, observation, and document analysis. This research’s result conclude that “Toko X” has applied internal control, but there is still some deficiencies that need correction so that it can overcome fraud problem that might happen in the future.